PENINGKATAN SENSITIVITAS KAKI DENGAN RANGE OF MOTION DIABETIC EXERCISE PADA PENDERITA DIABETES MELITUS TIPE II - Binarti Dwi Wahyuningsih; Umi Azizah Kusumaningrum (Jurnal EDUNursing, 2021)
Abstract                Diabetes mellitus (DM) is a metabolic disease whose prevalence continues to increase. One of the chronic complications of type II diabetes mellitus is hyperglycemia which tends to progress to diabetic ulcers which are preceded by decreased sensitivity in the feet, due to impaired perfusion and peripheral neuropathy. Range of Motion (ROM) exercises to reduce blood sugar circulation, prevent nerve damage, increase blood circulation and improve foot sensitivity, have not been widely practiced by patients with type II diabetes. The purpose of this study was to determine the effect of the range of motion diabetic exercise on the level of foot sensitivity using 10 gram monofilament in type II DM. The population is type II DM patients in the Peterongan Public Health Center, Jombang Regency. Sampling in this study using purposive sampling. Respondents in this study were 80 respondents. Data collection was carried out before and after treatment, namely the range of motion diabetic execise using a 10 gram monofilament foot sensitivity examination. Based on the results of the study, the measurement of foot sensitivity before treatment was obtained by more than some respondents (65%) with the category of no foot sensitivity, while the foot sensitivity after treatment was obtained by more than some respondents in the normal category, namely 48 respondents (60%). Based on data analysis, there is a difference in the level of foot sensitivity of patients with type II DM between the pretest and posttest, as indicated by the results of the Mann-Whitney test, namely p = 0.000. Regular range of motion diabetic exercise can improve lower extremity blood circulation, increase foot sensitivity and flex the peripheral nervous system, thereby reducing the risk of diabetic foot ulcers in type II DM patients. Keywords: range of motion diabetic, foot sensitivity, diabetes mellitus